2015
DOI: 10.1097/mib.0000000000000364
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Probiotics, Prebiotics, Synbiotics, and Psychobiotics in Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a group of diseases characterized by inflammation of the small and large intestine and primarily includes ulcerative colitis and Crohn's disease. Although the etiology of IBD is not fully understood, it is believed to result from the interaction of genetic, immunological, and environmental factors, including gut microbiota. Recent studies have shown a correlation between changes in the composition of the intestinal microbiota and IBD. Moreover, it has been suggested that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(90 citation statements)
references
References 98 publications
1
79
1
9
Order By: Relevance
“…IBD and COPD share common pathology relating to mucosal barrier disruption including an altered microbiome, immune dysfunction, altered epithelial cell function, and chronic inflammation [31, 41, 42]. Live microbial products are currently being tested for efficacy in IBD [43, 44]. Furthermore, a product that is prepared in a similar manner to KB, but produced from Escherichia coli, has shown evidence of efficacy in IBD patients [45] and is currently being investigated in clinical trials as a treatment for IBD.…”
Section: Discussionmentioning
confidence: 99%
“…IBD and COPD share common pathology relating to mucosal barrier disruption including an altered microbiome, immune dysfunction, altered epithelial cell function, and chronic inflammation [31, 41, 42]. Live microbial products are currently being tested for efficacy in IBD [43, 44]. Furthermore, a product that is prepared in a similar manner to KB, but produced from Escherichia coli, has shown evidence of efficacy in IBD patients [45] and is currently being investigated in clinical trials as a treatment for IBD.…”
Section: Discussionmentioning
confidence: 99%
“…2 Probiotics have been used in several disorders in populations ranging from infants to the elderly. Studies have shown probiotics are helpful in several diseases, including AAD 2 , the induction and maintenance of inflammatory bowel disease remission 3 , vaginal health 4 , necrotizing enterocolitis 5 , and nonalcoholic fatty liver disease. 6 However, a recent systematic review suggests that most probiotic strains may not prevent AAD in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…• competition for nutrients 2 • inhibition of epithelial/mucosal adherence of pathogens 2 • decreased colonic pH favoring the growth of nonpathogenic species 2 • defense against bacteriophages 3 • reduction of acute immune responses 3 …”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Experimental data and human studies have shown beneficial effects of prebiotic supplementation in different pathological conditions, including some gastrointestinal diseases such as liver diseases, IBD and chronic constipation[1517]. However, there is no consensus on the therapeutic efficacy of prebiotics in IBS[18].…”
Section: Introductionmentioning
confidence: 99%